Stability and catalytic activity of titanium oxy-nitride catalyst prepared by in-situ urea-based sol–gel method for the oxygen reduction reaction (ORR) in acid medium. (7th September 2015) - Seifitokaldani, A.; Savadogo, O.; Perrier, M.
Abstract: Titanium oxy-nitride is synthesized by the in-situ urea-based sol–gel method and is used as an electrocatalyst for the oxygen reduction reaction (ORR). Physicochemical and electrocatalytic properties of the prepared electrocatalysts are compared to those of titanium oxy-nitride electrocatalysts prepared by the other conventional sol–gel methods. Heat treatment effect on the nitrogen content, the BET surface area and the particle size of the electrocatalysts and consequently on the physicochemical and electrochemical properties of the electrocatalysts are systematically evaluated. This evaluation is supported by the chemical and electrochemical stability measurements through the CV and ICP-ToF-MS, bulk and surface chemical composition by the XRD, EDS, SEM and XPS and the electrocatalytic activity through the SSV and EIS results. From these correlations, the relation between the typical composition of the electrocatalyst and its high onset potential of 0.75 V is discussed. Highlights: TiON is prepared by different sol–gel methods. Their physicochemical and electrochemical properties are evaluated. TiON prepared by in-situ urea-based sol–gel (U) method shows superior stability. TiON prepared by U method shows better activity than other methods for the ORR.